2002
DOI: 10.1046/j.1440-1754.2002.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of hypoallergenic formula in the prevention of atopic disease among Asian children

Abstract: Exclusive feeding of hypoallergenic milk formula in the first 4 months of life has a protective effect in terms of the development of atopic dermatitis in the first 2 years of life, compared to feeding with cow's milk formula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 26 publications
4
73
0
Order By: Relevance
“…However, our results showed that the significantly less number of atopic dermatitis occurred in high risk infants fed with the partially hydrolyzed formula compared with the standard cow's milk formula, although this study did not compare the effects between the extensively hydrolyzed formula and the partially hydrolyzed formula. This data support the previous reports (4,8,13,14), in which the partially hydrolyzed formula prevented the development of either atopic disease or cow's milk allergy. In addition, no difference in the rate of growth was observed between the PHF and SF group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our results showed that the significantly less number of atopic dermatitis occurred in high risk infants fed with the partially hydrolyzed formula compared with the standard cow's milk formula, although this study did not compare the effects between the extensively hydrolyzed formula and the partially hydrolyzed formula. This data support the previous reports (4,8,13,14), in which the partially hydrolyzed formula prevented the development of either atopic disease or cow's milk allergy. In addition, no difference in the rate of growth was observed between the PHF and SF group.…”
Section: Discussionsupporting
confidence: 92%
“…Because the partially hydrolyzed formula is cheaper and more palatable than the extensively hydrolyzed formula, it was introduced for feeding high-risk infants who cannot tolerate the extensively hydrolyzed formula to prevent the development of atopic disease. The preventive effect of the partially hydrolyzed formula is still controversial because it contains a significant number of peptides with relatively high molecular weight compared with the extensively hydrolyzed formula (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a clinical trial involving 110 Singapore children with firstdegree atopic family history followed from birth to 30 months of age showed that the onset of AD was delayed when exclusively fed with PHF-W compared to CMF. (30) The cumulative eczema incidence in the PHF-W group compared to the CMF group was significantly lower at three months, six months, 12 months, 18 months and 24 months, and lower (28.3% vs. 43.9%),…”
Section: Allergology and Clinical Immunology And The European Societymentioning
confidence: 79%
“…(30) Furthermore, results of economic analyses based on the German Infant Nutritional Intervention (GINI) study demonstrated that PHF-W was cost-effective compared to CMF in high-risk, non-exclusively breastfed infants. (31)(32)(33)(34)(35)(36) A majority of these analyses were conducted from a Western perspective, except for two studies conducted in the Philippines (36) and Malaysia.…”
Section: Allergology and Clinical Immunology And The European Societymentioning
confidence: 99%
See 1 more Smart Citation